Answer:
Part A: X=0
Part B: x=0
Explanation:
Part A
(6^2)^X = 1
Applying the exponent rule:
![(a^b)^c = a^(bc)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ufhiydkf00hvvlo8pw7ek2ia2suastxeq2.png)
So, our equation will become:
![6^(2X) = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g5nvgd1xtiquytazo9uyrbgx5wombgznog.png)
We know if f(x) = g(x) then ln(f(x))= ln(g(x))
SO, taking natural logarithm ln on both sides and solving.
![ln(6^(2X)) =ln(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n27w2xknfzszw1ehvlj1962u8943ec1zqh.png)
We know,
Applying the rule,
![2Xln6 =ln(1)\\We\,\,know\,\,ln(1)=0\\2Xln6 =0\\Solving:\\X=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ddshuk5taq29eacjx1ftxehxfxh866ve0m.png)
Part B
(6^9)^x = 1
Applying the exponent rule:
![(a^b)^c = a^(bc)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ufhiydkf00hvvlo8pw7ek2ia2suastxeq2.png)
So, our equation will become:
![6^(9x) = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bqhs4f7h6lb8z1y2rxm98yeqmhs60wjn2l.png)
We know if f(x) = g(x) then ln(f(x))= ln(g(x))
SO, taking natural logarithm ln on both sides and solving.
![ln(6^(9x)) =ln(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l2gqathdeclbq8tqt3bgnecmi78t8on9p1.png)
We know,
Applying the rule,
![9xln6 =ln(1)\\We\,\,know\,\,ln(1)=0\\9xln6 =0\\Solving:\\x=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hbq74rwjrobb8vlmilz1n5atfyr3utim80.png)